Mapping the Research Landscape of 360-degree Visual Integrated Virtual Guides: A Bibliometric Review - Lingga Purwodani, Dio; Alfa Rabyn, Aswin (ITScience (Information Technology and Science), 2024)
Integrating 360-degree images into a building's virtual guide or receptionist is an emerging multidisciplinary study area that needs more focus. The first bibliometric analysis of recent research on the connection between virtual guides/receptionists and 360-degree visuals is presented in this paper. Scopus examined publications from 2019 to 2024 to determine subjects, productivity, impact, and collaboration. The findings indicate a rise in yearly production, with over 62 publications released in 2023 attesting to heightened research activity. Additionally, more recent papers have a larger citation effect, demonstrating their relevance today. Most prolific writers are from the US, the UK, and China. However, developing nations like Indonesia, Denmark, and Iran are among the top authoring nations, suggesting an increasing internationalisation. The West is the focal point of international cooperation. However, alliances with China are growing. This quantitative intelligence is a standard for upcoming research in this enormously promising field. Monitoring by bibliographers ought to go on as the conversation develops. The field of dental health, which is extensively utilised in the dental surgery process, surprisingly dominates the production of studies on this issue; this does not preclude the possibility of using 360-degree visual integration in diverse sectors. More involvement from marginalised stakeholders is required to responsibly develop 360-degree visual integration in virtual receptionists and guides.